Medico-political metaphors of counter-terrorism: The case of Turkey - BEYRİBEY, TUNCER (TAYLOR & FRANCIS LTD, 2020)
Medico-political metaphors can be defined as the organic imagining of a society (re)creating a normative distinction between identity and difference and mobilising specific types of political answers in which threats are constructed through organic language. Accordingly, society is made to resemble a body, thus creating a sense of unity, integrity and finitude, while terrorism is made to resemble a pathology that infects, weakens and ultimately destroys the healthy social body. In this narrative, terrorists are rendered as abnormal and external, and thus terrorism is depoliticised. It is fictionalised as a technical issue necessitating expert intervention, in a manner resembling the doctor-patient relationship. To date, there has been little research on the interaction between this organic understanding of society and the Turkish experience of counter-terrorism practices. Therefore, taking as its context the Syrian civil war, this article aims to analyse how medicopolitical metaphors in the counter-terrorism discourse of the Turkish government function as boundary-producing practices. The article critically assesses how medico-political metaphors in terrorism discourse (re)constitute a power relationship through abnormalisation, externalisation and depoliticisation, and thus contribute to Critical Terrorism Studies by highlighting how policy makers use medico-political metaphors to constitute a reality about terrorism in order to mobilise certain political responses.
Keywords: Counter-terrorism; Turkey; medico-political metaphors; Syrian Civil War; SECURITY; WAR; INTERVENTION; VIOLENCE